2016
DOI: 10.18805/lr.v0i0.7596
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced quality fodder production through grass-legume intercropping under arid eco-system of Kachchh, Gujarat

Abstract: Growth and development of huge livestock population of Kachchh is dependent on availability of quality fodder. The quality fodder shortage can be partially met out by cultivating grasses-legumes in intercropping systems. Therefore, this study with the aim of identifying best grass-legume intercropping system for enhanced quality fodder production was undertaken in randomized complete block design with three replications at Bhuj Gujarat, India. Dicanthium annulatum in combination of Clitoria ternatia and Stylos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…This result indicated that despite the low rate of inorganic fertilizer application, the N, P, and K nutrients were absorbed efficiently by shallot plants. The research by Kumar et al (2017) showed that appropriate crops planting in multiple cropping system could reduce the competition of space between crops and enhance light interception. The competition space could increase effectiveness of solar radiation, water, and nutrient absorption, thereby optimizing plant growth.…”
Section: Resultsmentioning
confidence: 99%
“…This result indicated that despite the low rate of inorganic fertilizer application, the N, P, and K nutrients were absorbed efficiently by shallot plants. The research by Kumar et al (2017) showed that appropriate crops planting in multiple cropping system could reduce the competition of space between crops and enhance light interception. The competition space could increase effectiveness of solar radiation, water, and nutrient absorption, thereby optimizing plant growth.…”
Section: Resultsmentioning
confidence: 99%
“…Bindhu et al [7] and Sarma et al [8] also recorded more seed yield in sole crop of sesame and Sesame: Black gram in 3:1 row ratio. Cultivation of sesame + green gram (1:1) gave 36.80% higher net return as sole sesame cropping [9].…”
Section: Mean Seed Yield Straw Yield Andmentioning
confidence: 99%
“…The swelling capacity was evaluated using the method of Kumar et al [23]. Swelling capacity was determined by weighing 20g of the flour into a cleaned, dried graduated cylinder.…”
Section: Determination Of Swelling Capacitymentioning
confidence: 99%
“…The fiber content of the sample was determined according to the method of AOAC, (23). Two (2) gram of the prepared samples were extracted using diethyl ether.…”
Section: Determination Of Crude Fiber Contentmentioning
confidence: 99%